Flavonoids from Polypodium hastatum as neuroprotective agents attenuate cerebral ischemia/reperfusion injury in vitro and in vivo via activating Nrf2 - Huankai Yao; Ruiqing Wu; Dan Du; Fengwei Ai; Feng Yang; Yan Li; Suhua Qi (Redox Report)
Objectives Cerebral ischemic stroke is a leading cause of death worldwide. Though timely reperfusion reduces the infarction size, it exacerbates neuronal apoptosis due to oxidative stress. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor regulating the expression of antioxidant enzymes. Activating Nrf2 gives a therapeutic approach to ischemic stroke.Methods Herein we explored flavonoids identified from Polypodium hastatum as Nrf2 activators and their protective effects on PC12 cells injured by oxygen and glucose deprivation/restoration (OGD/R) as well as middle cerebral artery occlusion (MCAO) mice.Results The results showed among these flavonoids, AAKR significantly improved the survival of PC12 cells induced by OGD/R and activated Nrf2 in a Keap1-dependent manner. Further investigations have disclosed AAKR attenuated oxidative stress, mitochondrial dysfunction and following apoptosis resulting from OGD/R. Meanwhile, activation of Nrf2 by AAKR was involved in the protective effects. Finally, it was found that AAKR could protect MCAO mice brains against ischemia/reperfusion injury via activating Nrf2.Discussion This investigation could provide lead compounds for the discovery of novel Nrf2 activators targeting ischemia/reperfusion injury.